Meningkatkan Kreatifitas dan Minat Bakat di Panti Rehabilitas Narkoba - Berlianti; Farah Adzraa Isty (Yayasan Literasi Sains Indonesia, 2022)
Drug rehabilitation is a repressive measure carried out for drug addicts. Rehabilitation measures are aimed at victims of narcotics abuse to restore or develop the physical, mental and social abilities of the sufferer concerned. In addition to recovering, rehabilitation is also a treatment or treatment for narcotics addicts so that addicts can recover from their addiction to narcotics. The rehabilitation phase aims to make it easier for those who have recovered to re-enter society with a good social adjustment. This social adjustment is formed through skills training or majors and group guidance. This skill, not only serves as a provision for work, but also as a discipline exercise. Creativity is the ability to express oneself creatively, although each resident has talent and creativity in different fields and in different levels. Talent is an innate ability, as a potential that still needs to be developed and trained in order to be realized.